Histological study of potassium 2-((4-amino-5-(morpholinomethyl)- 4H-1,2,4-triazole-3-yl)thio)acetate (PKR-173) corrective influence on the chickens liver state in the condition of tetracycline hepatitis - Shcherbyna, R. О.; Vashchyk, Ye. V.; Щербина, Роман Олександрович; Ващик, Є. В.; Щербина, Р. А.; Ващик, Е. В. (Запорізький державний медичний університет, 2018)
Despite great scientific progress in the sphere of hepatoprotectors development during recent years, the issues of hepatocytes protection and regeneration is relevant enough. In this aspect derivatives of heterocyclic systems are of great interest, in particular, of 1,2,4-triazole. The aim is histological study of the compound of potassium 2-((4-amino-5-(morpholinomethyl)-4H-1,2,4-triazol-3-yl)thio)acetate (PKR-173) corrective influence on the chickens liver under tetracycline hepatitis condition. Materials and methods. As an object of research potassium 2-((4-amino-5- (morpholinomethyl)-4H-1,2,4-triazol-3-yl)thio) acetate was used which is a water-soluble compound. Histological examination was carried out of the intact chickens liver (intact control); of the chickens after tetracycline administration (control pathology); of the chickens which before the administration of tetracy¬cline were administrated PKR-173 compound or thiotriazoline. All chickens were administrated tetracycline per os in the doze of 500 mg/kg for 5 days. PKR-173 compound and thiotriazoline were administrated per os for 3 days before tetracycline in doze of 150 mg/kg and 50 mg/kg respectively. Results. It has been noted that preventive administration of PKR-173 compound for chickens aged 7–18 days visually prevented the development of nonspecific morphological changes which are characteristic of acute moderately severe drug-induced bird’s liver injury. Compound PKR-173 contributed the organ histostructure normalization, prevented dystrophy manifestations, significantly reduced necrosis of hepatocytes and inflammatory reaction in the perivenular zone of triad system. Comparative drug thiotriazoline prevented hepatocytes dystrophy manifestation, in the vast majority of chickens contributed to hepatic plates structure restoration and inflammatory response reduction. In order to confirm the visual data according to the task, a semi-quantitative assessment of the PKR-173 and thiotriazoline corrective effect on chickens liver parenchyma morphological state was carried out. Conclusions. Analysis of the pathological process quantitative characteristics, which developed in the chicken liver after tetracycline administration and corrective influence of the investigated drugs on it, has shown that the PKR-173 compound significantly reduced the manifestations of all the pathological features detected for testing compared to control pathology. The PKR-173 compound is probably not inferior to comparative drug thiotriazoline by normalizing effect on the organ histostructure restoration and antidystrophic action intensity. The PKR-173 compound significantly outperforms the comparative thiotriazoline for anti-necrotic and anti-inflammatory effects. Незважаючи на великий науковий прогрес у галузі розробки гепатопротекторів, проблема захисту та регенерації гепатоци¬тів є актуальною. Інтерес у цьому аспекті викликають похідні гетероциклічних систем, а саме 1,2,4-тріазолу. Мета роботи – гістологічне дослідження корегувального впливу сполуки калій 2-((4-аміно-5-(морфолінометил)-4H-1,2,4-трі¬азол-3-іл)тіо)ацетат (ПКР-173) на стан печінки курчат в умовах тетрациклінового гепатиту. Матеріали та методи. Об’єкт дослідження – калій 2-((4-аміно-5-(морфолінометил)-4H-1,2,4-тріазол-3-іл)тіо)ацетат, що є водорозчинною сполукою. Виконали гістологічне дослідження печінки інтактних курчат (інтактний контроль); курчат, яким вводили тетрациклін (контрольна патологія); курчат, яким профілактично разом із тетрацикліном вводили сполуку ПКР-173 або тіотріазолін. Тетрациклін всім курчатам вводили per os у дозі 500 мг/кг протягом 5 діб. Сполуку ПКР-173 і тіатріазолін вводили per os протягом 3 діб до тетрацикліну в дозі 150 мг/кг та 50 мг/кг відповідно. Результати. Профілактичне введення сполуки ПКР-173 курчатам віком 7–18 діб візуально запобігає розвитку в печінці неспецифічних морфологічних змін, характерних для гострого помірно вираженого медикаментозного ураження. Сполука ПКР-173 сприяє нормалізації гістоструктури органа, запобігає проявам дистрофії, виразно знижує некроз гепатоцитів і запальну реакцію перивенулярно у системі тріад. Препарат порівняння тіотріазолін запобігає проявам дистрофії гепа-тоцитів, у більшості курчат сприяє відновленню балкового рисунка та зменшенню запальної реакції. Для підтвердження візуальних даних виконали напівкількісне (бальне) оцінювання коригувального впливу сполуки ПКР-173 та тіотріазоліну на морфологічний стан печінкової паренхіми курчат. Висновки. Аналіз кількісних характеристик патологічного процесу, що розвинувся в печінці курчат після введення тетра¬цикліну, та коригувального впливу на нього досліджених засобів показав: сполука ПКР-173 вірогідно знижує прояви всіх визначених для тестування ознак патології порівняно з контролем. Сполука ПКР-173 вірогідно не поступається препарату порівняння тіотріазоліну за нормалізуючим впливом на відновлення гістоструктури органа, виразністю дії, що запобігає розвитку дистрофії. Сполука ПКР-173 вірогідно перевищує препарат порівняння тіотріазолін за антинекротичним і проти¬запальним впливом. Несмотря на большой научный прогресс в области разработки гепатопротекторов, проблема защиты и регенерации гепатоцитов является весьма актуальной. Большую заинтересованность в данном аспекте вызывают производные гете¬роциклических систем, а именно 1,2,4-триазола. Цель работы – гистологическое исследование корректирующего воздействия соединения калий 2-((4-амино-5-(морфоли¬нометил)-4H-1,2,4-триазол-3-ил)тио)ацетат (ПКР-173) на состояние печени цыплят в условиях тетрациклинового гепатита. Материалы и методы. Объект исследования – калий 2-((4-амино-5-(морфолинометил)-4H-1,2,4-триазол-3-ил)тио)ацетат, который является водорастворимым соединением. Проведено гистологическое исследование печени интактных цыплят (интактный контроль); цыплят, которым вводили тетрациклин (контрольная патология); цыплят, которым профилактически до тетрациклина вводили соединение ПКР-173 или тиотриазолин. Тетрациклин всем цыплятам вводили per os в дозе 500 мг/кг в течение 5 суток. Соединение ПКР-173 и тиотриазолин вводили per os в течение 3 суток до тетрациклина в дозе 150 мг/кг и 50 мг/кг соответственно. Результаты. Отмечено, что профилактическое введение соединения ПКР-173 цыплятам в возрасте 7–18 суток визуально препятствует развитию в печени птиц неспецифических морфологических изменений, характерных для острого умеренно выраженного медикаментозного поражения. Соединение ПКР-173 способствует нормализации гистоструктуры органа, пре¬пятствует проявлениям дистрофии, определенно снижает некроз гепатоцитов и воспалительную реакцию перивенулярно в системе триад. Препарат сравнения тиотриазолин препятствует проявлениям дистрофии гепатоцитов, у большинства цыплят способствует восстановлению балочного рисунка и снижению воспалительной реакции. Для подтверждения ви¬зуальных данных проведена полуколичественная (балльная) оценка корректирующего воздействия соединения ПКР-173 и тиотриазолина на морфологическое состояние печеночной паренхимы цыплят. Выводы. Анализ количественных характеристик патологического процесса, развившегося в печени цыплят после введения тетрациклина, и корректирующего воздействия на него исследованных средств показал, что соединение ПКР-173 достоверно снижает проявления всех определенных для тестирования признаков патологии по сравнению с контрольной патологией. Соединение ПКР-173 достоверно не уступает препарату сравнения тиотриазолину по нормализующему влиянию на восстановление гистоструктуры органа, выразительности препятствующего развитию дистрофии действия. Соединение ПКР-173 достоверно опережает препарат сравнения тиотриазолин по антинекро-тическому и противовоспалительному воздействию.
Гістологічне дослідження корегувального впливу сполуки калій 2-((4-аміно- 5-(морфолінометил)-4H-1,2,4-тріазол-3-іл)тіо)ацетату (ПКР-173) на стан печінки курчат в умовах тетрациклінового гепатиту
Гистологическое исследование корректирующего воздействия калий 2-((4-амино-5-(морфолинометил)-4H-1,2,4-триазол-3-ил)тио)ацетата (ПКР-173) на состояние печени цыплят в условиях тетрациклинового гепатита
Keywords: 1,2,4-triazole; hepatitis; histological techniques; tetracycline; 1,2,4-тріазол; гепатит; гістологічне дослідження; тетрациклін; 1,2,4-триазол; гистологическое исследование; тетрациклин